The Prognostic Signature and Therapeutic Value of Phagocytic Regulatory Factors in Prostate Adenocarcinoma (PRAD) - Xin, Shiyong; Sun, Xianchao; Jin, Liang; Li, Weiyi; Liu, Xiang; Zhou, Liqing; Ye, Lin (Frontiers in Genetics, 2022)
There is growing evidence that phagocytosis regulatory factors(PRFs) play important roles in tumor progression, and identifying and characterizing PRF is particularly significant way for resolving the mechanisms of cellular phagocytosis in tumors. Therefore, our research aims to comprehensively characterize the disorder of PRFs in Prostate Adenocarcinoma (PRAD), screen and obtain key PRF, and construct tumor prognostic and therapeutic signatures based on key PRFs. Here, we firstly systematically described the expression of PRF in Prostate Adenocarcinoma (PRAD), and evaluated their expression patterns and their relationship with prognosis.We then analyzed prognostic phagocytic factors by Cox and Lasso analysis, and constructed a phagocytic factor-mediated Riskscore. We then divided the samples into two groups with significant differences in overall survival(OS) based on the Riskscore. Subsequently, correlation analysis was conducted between Riskscore and clinical features, immune infiltration level, immune characteristics, immune checkpoint expression and immunotherapy efficacy, etc. The above results confirmed that multilayer alterations of PRF were associated with the prognosis of patients with PRAD and the degree of macrophage infiltration,which may provide us a new idea for the therapy of PRAD in the future.